2007
DOI: 10.1088/0953-8984/19/37/373101
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanomaterials in biological systems

Abstract: This paper intends to reflect, from the biophysical viewpoint, our current understanding on interfacing nanomaterials, such as carbon nanotubes and fullerenes, with biological systems. Strategies for improving the solubility, and therefore, the bioavailability of nanomaterials in aqueous solutions are summarized. In particular, the underlining mechanisms of attaching biomacromolecules (DNA, RNA, proteins) and lysophospholipids onto carbon nanotubes and gallic acids onto fullerenes are analyzed. The diffusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 87 publications
0
51
0
Order By: Relevance
“…The association of a carbon nanotube with a surfactant such as sodium dodecyl sulfate (SDS) is pH dependent as is the actual surface area of a nanotube covered by the compound. 39 For example, what is the nature of a nanomaterial 'sequestered' in a lysosome characterized by a very acidic pH? Subtle differences in the physiological milieu of the nanotube (e.g., local ion concentration) would also be expected to alter subsequent particle disposition as well as toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The association of a carbon nanotube with a surfactant such as sodium dodecyl sulfate (SDS) is pH dependent as is the actual surface area of a nanotube covered by the compound. 39 For example, what is the nature of a nanomaterial 'sequestered' in a lysosome characterized by a very acidic pH? Subtle differences in the physiological milieu of the nanotube (e.g., local ion concentration) would also be expected to alter subsequent particle disposition as well as toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The p-p interaction between the polymers and the SWCNTs surfaces contributes to the solubilization of the SWCNTs [40]. Furthermore, previous studies had shown that the wrapping of SWCNTs by polymers was believed to be a general phenomenon, driven largely by thermodynamics to eliminate hydrophobic interface between the tubes and the aqueous medium [38,41].…”
Section: The Stabilization Mechanism Of Prepared Nanotube Dispersionsmentioning
confidence: 99%
“…The extraordinary properties of carbon nanotubes (CNTs) [1] have inspired their use in biosensors [2], drug delivery vehicles and tumour imaging [3,4], electrically conductive polymers [5] and concrete reinforcement [6].…”
Section: Introductionmentioning
confidence: 99%
“…Their fibrous structure raises concerns that they might have effects similar to those of asbestos [7,8]. Observations of the interactions of CNTs with animals, made both in vitro and in vivo, are sometimes contradictory [1,3,7]. Similarly, studies assessing CNT toxicity and bioavailability in plants have reported positive [9,10], negative [9,11] and even neutral [12][13][14] effects on germination and growth.…”
Section: Introductionmentioning
confidence: 99%